To hit or not to hit: large-scale sequence analysis and structure characterization of influenza A NS1 unlocks new antiviral target potential - Trigueiro-Louro, João M. (2020)
Influenza NS1 protein is among the most promising novel druggable anti-influenza target, based on its structure; multiple interactions; and global function in influenza replication and pathogenesis. Notwithstanding, drug development guidance based on NS1 structural biology is lacking. Here, we design a promising strategy directed to highly conserved druggable regions as a result of an exhaustive large-scale sequence analysis and structure characterization of NS1 protein across human-infecting influenza A subtypes, over the past 100 years. We have identified 3 druggable pockets and 8 new potential hot spot residues in the NS1 protein, not described before, additionally to other 16 sites previously identified, which represent attractive targets for pharmacological modulation. This study provides a rationale towards structure-function studies of NS1 druggable sites, which have the potential to accelerate the NS1 target validation. This research also contributes to a deeper comprehension and insight into the evolutionary dynamics of influenza A NS1 protein.